FRI0196 Relationship between bronchoalveolar lavage (bal) and high resolution-ct (hrct) findings in scleroderma lung disease. (1st June 2001) - La Corte, R; Santilli, D; Tieghi, R; Lo Monaco, A; Ravenna, F; Galeotti, R; Prandini, N; Trotta, F
Abstract : Background: Objectives: We assessed the presence of alveolitis by means of BAL and its correlations with HRCT findings in the diagnosis of systemic sclerosis (SSc)-related interstitial lung disease (SSc-ILD). Methods: 43 nonsmoking patients (pts) with SSc, with a mean age of 54.62 ± 2.08 years (range 23–74), underwent to: bronchoscopy with BAL according to the 1990 American Thoracic Society guidelines; 1 lung HRCT, graded according to a scoring system proposed by Warrick et al .; 2 and SSc-related antibodies testing. Results: Patients with alveolitis (A) and those without alveolitis (NA), divided according to BAL results, were comparable as to mean age and duration of disease, to the prevalence of diffuse or limited subset of disease, to mean values of skin score and to the results of examinations with respiratory function tests, diffusing capacity for carbon monoxide, and inhaled 99mTc-DTPA for the measure of alveolar clearance rate performed as part of the whole clinical assessment. BAL showed the presence of alveolitis in 18/43 pts (41.8%) with cell profiles so distributed: lymphocytic (L) in 5/18 pts (27.7%); eosinophilic (E) in 1/18 (5.5%); pure neutrophilic (N) in 5/18 (27.7%) and a mixed pattern (3 N+L, 3 N+E, 1 N+L+E) in 7/18 (38.8%). Both "total HRCT" score (14.3 ± 1.2 vs 9.2 ± 1.2; p = 0.01) and "severity of disease" score (8.8 ± 0.8 vs 6.0 ± 0.8; p = 0.02) yelded significantly higher values in A pts compared with NA pts. Among HRCT abnormalities, only "honeycombing" (HC) was significantly more frequent in A pts (p = 0.033); while the presence of "ground glass" (GG), "irregular pleural margins", "septal/subpleural lines" and "subpleural cysts" showed no differences between A and NA pts. Anti Scl-70 positivity was more prevalent in A pts (p = 0.015) and, whether or not alveolitis was present, it correlated with higher "total HRCT" scores (p = 0.039). Conclusion: Seemingly, GG cannot be unambiguously considered as the radiographic sign of alveolitis, since the latter is more prevalent in patients with HC which so, far from being the equivalent of a purely fibrotic outcome, could represent pathologic lung tissue that still retains some ongoing and potentially treatable inflammatory activity. Moreover, we confirm the role of anti Scl-70 as a negative prognostic marker associated with SSc-ILD. References: Am Rev Respir Dis. 1990;142:481 J Rheumatol. 1991;18:1520